SOCIAL AND DIGITAL INCLUSION IN YOUTH AND ADULT EDUCATION: AN INTERVENTION PROGRAM CONTRIBUTIONS - Mendes Amparo, Matheus Augusto [UNESP]; Schlunzen Junior, Klaus [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2019)
The paper has as theme the Teaching Young and Adult Education (EJA) and the importance of the social and digital inclusion for this public. The problem of the research is: how to develop an intervention program in computer science focused on Youth and Adult Education having in mind the social and digital inclusion of learners? The general objective was to develop and analyze a computer intervention program in Young and Adult Education. The research has a qualitative approach and it has used as its technical procedure the interventional research. For the data collection it was used the interview, the form and notes, the records were made by means of filling out diaries and pictures and the data analysis was performed by content analysis. The investigation final results indicate which way an intervention program can be developed in Informatics for the EJA. It was also noted that the intervention program contributed to the learning and development of social and digital inclusion of the research subjects, though it was only a beginning.
Keywords: Young and Adult Education; Computers in Education; Social and digital inclusion